Impact of physical activity on the quality of life of residents of a social welfare home - Bartosz Kulikowski; Krzysztof Zdziarski; Krzysztof Antczak (Kazimierz Wielki University, 2019)
Introduction: Physical activity is the main factor in strengthening health in every phase of life and an important element in connection with the quality of life. When assessing the quality of life of older people it is necessary to take into account various aspects related to health and physical and psychological well-being as well as the indicators of social functioning. The aim of the work is to assess the impact of physical activity on the quality of life of social welfare home residents. Material and methods: The research was carried out with the help of two questionnaires used to assess the quality of life (WHOQOL-BREF, SF-36) and the IPAQ questionnaire thanks to which the physical fitness of patients was assessed. Results: Women are more likely to become more physically active. The somatic sphere has the most connection with physical activity. The subjects showing the sufficient physical activity are characterized by the highest scores on the psychological sense scale. Conclusions: Physical activity is one of the main factors determining the quality of life of older people.